Web Application Design for Service Quality Analysis with SERVQUAL method - Febriansyah, Moh Fajar; Dako, Rahmat Deddy Rianto; Lahay, Idham Halid; Dako, Amirudin Yunus; Nasibu, Iskandar Zulkarnain; Musa, Wahab (Jambura Journal of Electrical and Electronics Engineering, 2025)
Quality measurement consists of three stages: data collection, data testing, and data processing. In general, each of these stages requires a significant amount of time. The process starts with the data collection stage, which may involve questionnaires. Distributing, completing, and collecting questionnaires will take a considerable amount of time. Similarly, the second stage, data testing, is carried out to validate whether the data obtained in the previous stage is accurate or not. The third stage will only take place once the data from the first two stages is deemed valid. Data processing itself also requires a significant amount of time because the data must be entered individually. Based on this issue, a system is needed that can integrate all three stages to expedite the overall process. The objective of this research is to design a web-based service quality measurement application that can integrate all three stages simultaneously. The data processing stage in this research uses the Service Quality method, also known as the SERVQUAL method. The application design is carried out using the Systems Development Life Cycle (SDLC) development method with the prototype model. Application testing is conducted using three stages: alpha testing, beta testing, and usability testing. Alpha testing refers to internal testing of the application. Beta testing, using the black-box method, resulted in a score of 83.33%. Usability testing, using the System Usability Scale (SUS), obtained a score of 81, which falls within the Acceptability Range. In the Adjective Range category, the application was rated as excellent, and on the grade scale, it was rated as B.Pengukuran kualitas memiliki 3 tahapan, yakni pengumpulan data, pengujian data, dan pengolahan data. Secara umum, setiap tahapan ini dilalui dengan durasi waktu yang lama. Berawal dari tahapan pengumpulan data misalnya dengan kuesioner. Penyebaran, pengisian maupun pengumpulan kuesioner akan memerlukan waktu yang tidak singkat. Demikian pula, menuju ke tapanan yang kedua yaitu pengujian data, dimana tahapan ini dilakukan untuk menguji apakah data yang diperoleh pada tahapan sebelumnya valid atau tidak.  Tahapan ketiga akan dilakukan jika data yang diperoleh pada dua tahapan sebelumnya sudah valid. Proses pengolahan data pun akan memerlukan waktu yang cukup lama karena datanya akan dimasukan satu per satu. Berdasarkan permasalahan ini maka diperlukan sebuah sistem yang dapat mengintegrasikan ketiga tahapan tersebut untuk mempercepat keseluruhan proses. Tujuan penelitian ini adalah merancang sebuah aplikasi pengukuran kualitas layanan berbasis web yang dapat mengintegrasikan ketiga tahapan ini sekaligus. Tahapan pengolahan data pada penelitian ini menggunakan metode Service Quality atau lebih dikenal dengan metode SERVQUAL. Perancangan aplikasi dilakukan menggunakan metode pengembangan Systems Development Life Cycle (SDLC) dengan model prototype. Pengujian aplikasi dilakukan menggunakan tiga tahapan, yaitu alpha testing, beta testing, dan tes usabilitas. Alpha testing yaitu pengujian aplikasi secara internal. Beta testing menggunakan metode blackbox mendapatkan hasil sebesar 83,33%. Pengujian tes usabilitas menggunakan System Usability Scale (SUS) dan mendapatkan skor 81, yang masuk pada tingkat Acceptability Range. Pada kategori Adjective Range, aplikasi dinilai berada pada tingkatan excellent, dan pada grade scale berada pada tingkatan B.